Misinformation and right to self-determination - Elena Llorca-Asensi; María Elena Fabregat; Raúl Ruiz-Callado (Oñati Socio-Legal Series)
The true meaning and scope of laws is unknown to most of the population, as evidenced by various studies on legal culture around the world. Therefore, whenever false or inaccurate information about legal issues is disseminated, the impact on public opinion can be enormous. This study shows that this has happened, in the so-called Catalan conflict, with respect to the right to self-determination. Thus, while legal experts deny that Catalonia is entitled to invoke the "right to self-determination of peoples" to obtain its independence, some civil associations, the media and, above all, political leaders, claim the opposite or make inaccurate statements which, in an attempt to deny this right, increase popular confusion. As a result, the current polarized discourse around the self-determination of Catalonia is built, at least in part, on the erroneous legal knowledge of three quarters of citizens.